Concise Chemoenzymatic Total Synthesis and Identification of Cellular Targets of Cepafungin I - Amatuni, Alexander (Cell Chem Biol, 2020)
The natural product cepafungin I was recently reported to be one of the most potent covalent inhibitors of the 20S proteasome core particle through a series of in vitro activity assays. Here, we report a short chemoenzymatic total synthesis of cepafungin I featuring the use of a regioselective enzymatic oxidation to prepare a key hydroxylated amino acid building block in a scalable fashion. The strategy developed herein enabled access to a chemoproteomic probe, which in turn revealed the exceptional selectivity and potency of cepafungin I towards the β2 and β5 subunits of the proteasome. Further structure-activity relationship studies suggest the key role of the hydroxyl group in the macrocycle and the identity of the lipid tail in modulating the potency of this natural product family. This study lays the groundwork for further medicinal chemistry exploration to fully realize the anticancer potential of cepafungin I.